2019
DOI: 10.1029/2018jg004796
|View full text |Cite
|
Sign up to set email alerts
|

Advances in the Eddy Covariance Approach to CH4 Monitoring Over Two and a Half Decades

Abstract: Receding permafrost may expose the largest store of sequestered carbon to microbes ready to convert it to greenhouse gases. The fluxes of biogenic gases associated with boreal wetlands have historically been difficult to measure, limiting our understanding of what may happen as permafrost thaws. The many difficulties in working in high‐latitude climates have dramatically limited our understanding on the spatial and temporal distribution of fluxes and what is likely to change with a warming climate. The use of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 81 publications
4
27
0
Order By: Relevance
“…Previous synthesis studies also observed a significant, but weaker, relationship between soil temperature and average CH 4 emissions across sites, explaining <15% of the variation in CH 4 flux in those studies (Olefeldt et al 2013;Yvon-Durocher et al 2014). However, our findings are consistent with numerous site-level studies that report a strong correlation between wetland CH 4 emissions and temperature, with nearly 95% of all EC studies reporting a significant relationship between temperature and CH 4 f lux (Morin 2018). Across sites, Peltola et al (2019) found that the most important predictor in a random forest model used to upscale EC CH 4 emissions across northern latitudes was temperature, again highlighting the importance of temperature in regulating CH 4 emissions within and across sites.…”
Section: Resultssupporting
confidence: 91%
See 3 more Smart Citations
“…Previous synthesis studies also observed a significant, but weaker, relationship between soil temperature and average CH 4 emissions across sites, explaining <15% of the variation in CH 4 flux in those studies (Olefeldt et al 2013;Yvon-Durocher et al 2014). However, our findings are consistent with numerous site-level studies that report a strong correlation between wetland CH 4 emissions and temperature, with nearly 95% of all EC studies reporting a significant relationship between temperature and CH 4 f lux (Morin 2018). Across sites, Peltola et al (2019) found that the most important predictor in a random forest model used to upscale EC CH 4 emissions across northern latitudes was temperature, again highlighting the importance of temperature in regulating CH 4 emissions within and across sites.…”
Section: Resultssupporting
confidence: 91%
“…More sites in key regions. We expect the number of flux towers measuring CH 4 fluxes will continue to grow (Chu et al 2017;Pastorello et al 2017;Morin 2018), but our compilation of EC CH 4 flux sites highlights key underrepresented regions where future flux towers are needed or where more efforts are needed for existing but nonreporting towers to contribute to FLUXNET (Fig. 1).…”
Section: Ec Flux Data Quality Assessmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Although a series of biophysical variables (e.g., T air , soil temperature, radiation, WTD, salinity, NEE, GPP, Re, and LE) have been identified as important drivers of F CH4 , their relative significance could vary across different ecosystems and timescales (Morin, 2019). Our results of correlation analysis revealed the importance of a number of key variables (e.g., T air , soil temperature and salinity) in driving F CH4 , which might be confounded by the high collinearity among the drivers (Table 4).…”
Section: Discussionmentioning
confidence: 99%